Beyond the literal: fiction as a tool for leisure inquiry. Issue 5 (20th October 2021) - Dunlap, Rudy; Harmon, Justin
ABSTRACT: Using fictional expression, this special issue provokes visions of leisure that are not immediately accessible to empirical analysis, but which nevertheless compel the exercise of our moral imagination. Echoing Pinker's (2012) arguments, we contend that fictional expression opens our imagination to previously inaccessible spaces, and allows our speculative faculties to extend empirical knowledge to situations that lie beyond personal experience and conventional research questions. Drawing on Bruner's (1986) explication of paradigmatic and narrative ways of knowing, the special issue recruits readers as co-creators in the psychic narrative of leisure that lies beyond the literal words on the page.